Detecting hidden time patterns in football - Jonsson, G.; Borrie, A.; Bjarkadottir, S. (Book of abstracts of the 6th annual congress of the European College of Sport Science, 15th congress of the German Society of Sport Science. Cologne, 24-28 July 2001, 2001)
Vorstellung einer Software, mit der in Sportspielen bisher nicht erkennbare zeitliche Handlungsstrukturen verdeutlicht werden können. Mehr Informationen unter: http://www.noldus.com/events/mb2000/program/abstracts/jonsson2 .html